Cardiotoxicity in Ewing- and osteosarcoma: a 40 year experience from a tertiary sarcoma center. (3rd October 2022) - Heemelaar, J C; Al Jaff, A A M; Polomski, E A S; Evenhuis, R E; Van De Sande, M A J; Gelderblom, A J; Speetjens, F M; Mertens, B J A; Jukema, J W; Antoni, M L
Abstract: Background: While malignant bone sarcoma is rare in the general population, it is the second most common malignancy among children and young adults. (Neo)adjuvant systemic treatment carries a significant risk of cardiotoxicity (CTx) in the form of late-onset left ventricular dysfunction and heart failure. There are several long-term follow up protocols in place for survivors of childhood and adolescent cancers, but when sarcoma is diagnosed at higher age the best follow up practice is less clear and there is little known about the long-term risk and mode of onset of CTx. Purpose: To evaluate the effect of age at sarcoma diagnosis on incidence of cardiotoxicity (CTx) and time-to-CTx. Methods: This single-center retrospective analysis of CTx of sarcoma treatment was performed at a tertiary sarcoma center in the Netherlands (Leiden University Medical Center, LUMC) among patients with a high-grade osteosarcoma (OS) and Ewing sarcoma (ES). All patients were diagnosed and treated over a 36-year period (1982 and 2018) at LUMC, and followed up until August 2021. The main inclusion criterium was exposure to doxorubicin-containing chemotherapy regimens. The exposure of interest was age at cancer diagnosis with a cut-off for older age at ≥30 years (age30+) The primary study endpoint was incident clinically relevant CTx at follow up, defined as composite of pharmacological heart failure (HF) treatment initiation, HF admissions and ICD implantation. Cause-specific Cox modeling was performed to calculate the hazard ratio (HR) of age group and incidence of both the primary study endpoint and competing risk of all cause death. Results: The study population consisted of 556 patients (69.0% OS, 31.0% ES) with a median age at sarcoma diagnosis of 19 [p25-p75: 15–30] years and the majority of patients were male (60.4%). 146 patients were in the age30+ group (26.3%). In a median follow up time of 5.5 [2.0–13.2] years, 27 patients reached the primary endpoint (4.9%). In 7/27 cases an urgent HF hospitalization was the first manifestation of HF and the remaining cases met the primary endpoint due to pharmacological HF treatment imitation. At the end of follow up mortality was 49.3% of patients. The vast majority of patients died of malignancy-related causes (95.6%). When correcting for female sex and sarcoma type, age30+ at sarcoma diagnosis was associated with a near 3.5 fold increased risk of HF compared to when sarcoma was diagnosed below 30: HR 3.39 (95% CI: 1.57–7.31), p=0.019. For the age30+ group whom experienced CTx the time-to-event was shorter compared to those diagnosed below 30 years at: respectively 5.5 years vs. 12.6 years (see Figure 1; Wilcoxon rank-sum test: p=0.012). Conclusions: Sarcoma patients above 30 years at diagnosis have an increased risk of CTx and time to development of CTx was significantly shorter. Funding Acknowledgement: Type of funding sources: None.